2022
DOI: 10.1039/d1sc06098h
|View full text |Cite
|
Sign up to set email alerts
|

Growth kinetics determine the polydispersity and size of PbS and PbSe nanocrystals

Abstract: A library of thio- and selenourea derivatives is used to adjust the kinetics of PbE (E = S, Se) nanocrystal formation across a 1000-fold range (kr = 10-1–10-4 s-1), at...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
37
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 25 publications
(45 citation statements)
references
References 65 publications
(142 reference statements)
5
37
1
Order By: Relevance
“…Spectroscopic and X-ray scattering characterization of these solutes suggests a molecular complex with formula [(PbS)(Pb(oleate) 2 )] 2 . 14 Collectively, the NMR, UV-vis, and X-ray scattering kinetics data support a stepwise process where the lead oleate and thiourea are converted to solutes that accumulate and are then consumed by nanocrystal growth.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…Spectroscopic and X-ray scattering characterization of these solutes suggests a molecular complex with formula [(PbS)(Pb(oleate) 2 )] 2 . 14 Collectively, the NMR, UV-vis, and X-ray scattering kinetics data support a stepwise process where the lead oleate and thiourea are converted to solutes that accumulate and are then consumed by nanocrystal growth.…”
Section: Resultsmentioning
confidence: 87%
“…Reactions performed at lower temperatures display even longer nucleation times. 14 Interestingly, the nucleation rate decays as the solute concentration climbs to its maximum value. The inverse correlation between nucleation rate and solute concentration is counterintuitive, however, a variety of factors may directly or indirectly inuence the nucleation rate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sugimoto and others solved this mass balance under the assumption of burst nucleation and found that the final particle number is proportional to Q and inversely proportional to the growth rate. The above linear dependence on Q is valid for high growth rates. , For lower growth rates (e.g., in the presence of surfactants), a square root dependence is predicted . Such relations between precursor conversion rate and particle number have been confirmed by ample experimental data; ,,,,,,, see Figure C for an example of PbS nanocrystals.…”
Section: Crystallization Into Nanocrystalsmentioning
confidence: 76%
“…(C) Relation between final number of particles and monomer generation rate, exemplified here with the concentration of PbS nanocrystals at different temperatures. Data replotted from ref .…”
Section: Crystallization Into Nanocrystalsmentioning
confidence: 99%